Penguatan Karakter Religiositas Melalui Pembelajaran Teks Cerita Pendek Dengan Menggunakan Model Bermain Peran - Rizal Ibrahim Aji; Fiki Setiawan; Syamsurrijal Syamsurrijal (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This research aims to determine a role-playing strategy model in strengthening religious character through learning short story texts. The research method used is the Design Based Research (DBR) method. The research stage is divided into five parts, namely problem identification, product development formulation, product design and development, product testing, and communicating results. The results of observing teacher activities through role playing strategies show that the score obtained from observer one is 92 in the very good category, while the score obtained by observer two is 90 in the very good category. The results of observing students' activities through role playing strategies showed that the score obtained from observer one was 94 in the very good category, while the score obtained by observer two was 92 in the very good category. Based on the results of data analysis obtained from students' self-assessment questionnaires regarding strengthening religious character through learning short story texts using role-playing strategies. The total score obtained by students was 1163 and the average number obtained from 15 students was 77 with a percentage of 96%. To strengthen the character of religiosity in students, teachers must be more creative in cultivating the value of religious character in students through the learning process.